Protecting clinical trial participants and study integrity in the age of social media. Issue 24 (17th October 2018) - Lynch, Holly Fernandez; Largent, Emily A.; Joffe, Steven; DeMichele, Angela M.
Abstract : Social media communication among clinical trial participants has the potential to pose risks to their safety and to trial integrity. The Social Media ADEPT framework may help mitigate that potential by encouraging investigators and patient partners to work together toA ssess social media risks, D esign studies to minimize those risks, E ducate participants, P reempt problems, andT ake additional steps as needed, such as intervening when problems arise.